Fecal incontinence in patients with spina bifida: The target is the rectum. Issue 3 (26th September 2017) - Brochard, Charlène; Ropert, Alain; Peyronnet, Benoît; Ménard, Hélène; Manunta, Andréa; Neunlist, Michel; Bouguen, Guillaume; Siproudhis, Laurent
Abstract : Aims: The prevalence rate of severe fecal incontinence (FI) in adults with spina bifida (SB) is high. The physiological basis of FI in SB has not been clearly established, which contributes to inadequate care. The aim was to better characterize a large cohort of adults with special consideration of anorectal physiology. Methods: A multidisciplinary team from a French referral centre for SB prospectively collected data on patients who had an anorectal manometry. Factors associated with severe FI (Cleveland clinical incontinence score ≥ 9) were assessed in a multivariate analysis model. Results: A total of 132 adults with SB (sex ratio M/F: 55 [41.7%]/77 [58.3%]; mean age of 38.2 [11.6] years old) were assessed. Among these patients, 83/132 (62.9%) suffered from severe FI. Rectal perception was not evaluable among 17 patients who had a latex allergy. Overall, 29/115 (25.2%) had maximal tolerable volume (MTV) > 330 mL or no sensation. The absence of anal canal sensitivity, MVT > 330 mL and the amplitude of the recto‐anal inhibitory reflex (RAIR) >75% after a rectal isovolumic inflation of 50 mL were significantly associated with severe FI in the multivariate analysis model. Neither neurological level nor other neurological features were associated with severe FI. Conclusions: This study showed that FI in patients with SB is mainly associated with rectal abnormalities. This should be taken into consideration to improve incontinence management of patients with SB.